Responsabilidade social empresarial: o consumidor como motivador de iniciativas: estudo de caso 'Conexão Belterra' conduzido pela empresa Vivo - Rocha, Michel da (2013)
According to the Marketing´s specific literature, the topic of Corporate Social Responsibility (CSR) has often been driven by companies in order to anticipate the behavior of consumers who are increasingly demanding this type of initiative, setting up as an act of Social Marketing. Research indicates that, despite the claiming to be prone to consider the social attitudes of the companies in their purchasing choices, the consumer does not act in accordance with their stated intentions, creating a gap between intention and purchase behavior. The objective of this dissertation, taking as its starting point the observation of the Vivo´s deployment of 3G coverage in the community of Belterra-PA is to check the importance of stakeholder consumer regarding the context of Corporate Social Responsibility through two observation points: from the companies perspective, verifying if the consumer is considered among the motivators for managers at the time of investment decision in Corporate Social Responsibility actions, and from the consumers perspective, verifying if the Brazilians consumers value and legitimize these initiatives through their buying behavior. We start from an extensive literature review about Corporate Social Responsibility in order to trace how this topic has been linked to the field of Marketing. Regarding to the companies motivators, we wrote a case study about the project “Conexão Belterra” having as information sources magazines, blogs, company executives’ in-depth interviews and academic work research (Cruz, 2002). Despite the observation this action is aligned with its mission and objective, the company did not consider the consumer as a key motivator when implementing this CSR initiative. In relation to the consumer behavior, we locate the Öberseder, Schlegelmilch e Gruber (2011) paper, whose theoretical and methodological approach, as well the roadmap for research, served us as a guide for the development of our own empirical research. We conducted a qualitative study with 16 indepth interviews in order to explore how consumers’ perceptions about SR interfere in their evaluation process as purchasing behavior. Our results largely corroborate in the same direction of the results of Öberseder, Schlegelmilch e Gruber (2011), although bringing new specific socio-cultural aspects regarding Brazil contexto.